Reduction of Charge Traps and Stability Enhancement in Solution-Processed Organic Field-Effect Transistors Based on a Blended n-type Semiconductor - Campos, Antonio; Riera-Galindo, Sergi; Puigdollers, Joaquim; Mas-Torrent, Marta (ACS applied materials & interfaces, 2018)
Solution-processed n-type organic field-effect transistors (OFETs) are essential elements for developing large-area, low-cost, and all organic logic/complementary circuits. Nonetheless, the development of air-stable n-type organic semiconductors (OSC) lags behind their p-type counterparts. The trapping of electrons at the semiconductor-dielectric interface leads to a lower performance and operational stability. Herein we report printed small molecule n-type OFETs based on a blend with a binder polymer, which enhances the device stability due to the improvement of the semiconductor-dielectric interface quality and a self-encapsulation. Both combined effects prevent the fast oxidation of the OSC. Additionally, a CMOS-like inverter is fabricated depositing a p-type and n-type OSCs simultaneously.